Let a < b < c be the three real roots of the equation 3 x 3 − 3 5 x 2 + 5 0 0 = 0 .
Find ( b c ) 2 5 0 0 2 + ( a c ) 2 5 0 0 2 + ( a b ) 2 5 0 0 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using Vieta's Formula we have:- a + b + c = 3 3 5 a b + b c + c a = 0 a b c = 3 − 5 0 0
( b c ) 2 5 0 0 2 = ( 3 a − 5 0 0 5 0 0 ) 2
Similarly we will get a equation at last which is equal to:-
9 ( a 2 + b 2 + c 2 ) 9 [ ( a + b + c ) 2 − 2 ( a b + b c + c a ) ] = 9 ( 3 3 5 ) 2 = 1 2 2 5
Another way is to determine the roots. As we solve the equation we get x=-10/3, 10, and 5 Just plug in those values
Problem Loading...
Note Loading...
Set Loading...
E = ( b c ) 2 5 0 0 2 + ( a c ) 2 5 0 0 2 + ( a b ) 2 5 0 0 2 .
⟹ E = ( 5 0 0 ) 2 ( ( a b c ) 2 a 2 + ( a b c ) 2 b 2 + ( a b c ) 2 c 2 ) .
Using a b c = 3 5 0 0 we get
E = ( 5 0 0 ) 2 ( ( 5 0 0 ) 2 9 a 2 + ( 5 0 0 ) ) 2 9 b 2 + ( 5 0 0 ) 2 9 c 2 ) .
E = 9 ( a 2 + b 2 + c 2 )
E = 9 ( ( a + b + c ) 2 − 2 ( a b + b c + c a ) )
Using a + b + c = 3 3 5 and a b + b c + c a = 0 we get
E = 9 ( ( 3 3 5 ) 2 − 2 × 0 ) = ( 3 5 ) 2 = 1 2 2 5